The Economics of the Name Change: Long-term Adjustments towards EU/NATO or Short-term Resolution of Political Uncertainty? - Srbinoski, Bojan; Poposki, Klime; Dencic-Mihajlov, Ksenija; Pavlovic, Milica (Organizations and Markets in Emerging Economies, 2021)
North Macedonia and Greece resolved the 27-year country name dispute and removed the main hurdle for North Macedonia to start the accession processes towards the EU and NATO. The paper analyzes the stock market movements around several events related to the name issue resolution to uncover whether Macedonian companies experienced stock price adjustments according to the long-term benefits/costs of joining the EU/NATO. The dynamics of the market reactions suggest that the investors reacted systematically to the short-term political uncertainty created around the referendum rather than to the long-term perspectives of the EU/NATO integration. We integrate the knowledge from the literature which explores stock market reactions to EU enlargement/exit and political elections and provide contributions for researchers and policymakers.